2010
DOI: 10.1017/s0950268810000075
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of livestock-associated MRSA in broiler flocks and risk factors for slaughterhouse personnel in The Netherlands

Abstract: SUMMARYTo determine methicillin-resistant Staphylococcus aureus (MRSA) carriage in poultry and slaughterhouse personnel, 40 Dutch broiler flocks, in six slaughterhouses and 466 personnel were sampled. Of the employees, 26 were positive (5 . 6 %), indicating a higher risk of exposure when compared to the general Dutch population (0 . 1 %). This risk was significantly higher for personnel having contact with live animals (5 . 2 %) -especially hanging broilers on the slaughterline (20 . 0%) -than for all other pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
5
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(151 citation statements)
references
References 27 publications
5
126
5
1
Order By: Relevance
“…This study demonstrated that ST9 MRSA is the major livestock-associated MRSA (LA-MRSA) in pigs. In China, the predominant spa type in this lineage was reported to be t899, while those identified in Thailand, Malaysia, and The Netherlands were t337, t4358, and t1430, respectively (9,12,13). Our data showed that the predominant MSSA isolates carried by pigs were also spa t899, and they have multidrug resistance profiles similar to their MRSA counterparts.…”
Section: Figmentioning
confidence: 53%
“…This study demonstrated that ST9 MRSA is the major livestock-associated MRSA (LA-MRSA) in pigs. In China, the predominant spa type in this lineage was reported to be t899, while those identified in Thailand, Malaysia, and The Netherlands were t337, t4358, and t1430, respectively (9,12,13). Our data showed that the predominant MSSA isolates carried by pigs were also spa t899, and they have multidrug resistance profiles similar to their MRSA counterparts.…”
Section: Figmentioning
confidence: 53%
“…The strains were both human and animal associated. Other studies demonstrated MRSA in raw chicken meat (Kitai et al, 2005;Lee, 2006;Dohoo et al, 2009) and broilers at slaughterhouses (Mulders et al, 2010). LA-MRSA isolates in poultry have previously been found in the Netherlands (Leenders et al, 2007;Geenen et al, 2012) and Belgium (Nemati et al, 2008;Persoons et al, 2009;Vanderhaeghen et al, 2010a;Pletincks et al, 2011).…”
Section: Introductionmentioning
confidence: 88%
“…The horse strains were nearly all (94%) samples from diseased horses that visited the Utrecht University equine clinic, the remaining 6% being from healthy horses. The chicken isolates were obtained from a study in six broiler slaughterhouses, where broilers from 40 flocks arriving at the slaughterhouses were sampled in the pharynx after stunning (21). S. aureus isolates were spa typed by the RIVM according to the method of Harmsen et al (22).…”
Section: Methodsmentioning
confidence: 99%